Green practices as a path towards the sustainability: Evidence from Portuguese companies - Wellington Alves; Ângela Silva; Helena Sofia Rodrigues (Business Systems Research (BSR), 2020)
Background: In the last years, the concept of sustainability has been receiving global attention from academics, the public sector and practitioners. The high level of industrialization has contributed to the increase of environmental impacts on the environment and the society. To give a sustainable answer to the industrial sector, more strategies aimed at reducing the environmental and social impacts should be considered. Objectives: This research aims to evaluate the level of environmental practices in a set of companies from the northern region of Portugal. Methods/Approach: In order to achieve the objective of this research, several steps were taken, and approach is mainly based on an online questionnaire administered in a set of companies. Results: The initial results show that companies are progressing when it comes to the implementation of measures and practices related to sustainability. Conclusions: The study resulted in suggestions for consulted companies, namely the need for effective mechanics to ensure compulsory but expedite environmental procedures along with procedures control, which is a key factor in ensuring sustainable and green practices.
Keywords: L16; 330; green practices; sustainability; Portugal; statistical analysis